2011
DOI: 10.1109/tc.2011.68
|View full text |Cite
|
Sign up to set email alerts
|

QoS-Aware Fault-Tolerant Scheduling for Real-Time Tasks on Heterogeneous Clusters

Abstract: Abstract-Fault-tolerant scheduling plays a significant role in improving system reliability of clusters. Although extensive fault-tolerant scheduling algorithms have been proposed for real-time tasks in parallel and distributed systems, quality of service (QoS) requirements of tasks have not been taken into account. This paper presents a fault-tolerant scheduling algorithm called QAFT that can tolerate one node's permanent failures at one time instant for real-time tasks with QoS needs on heterogeneous cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Some works support fault tolerance in cloud environments by scheduling backup copies of failed tasks. For example, QAFT [32] schedules primary and backup copies of tasks on different cloud nodes, considering different QoS levels for the tasks and different speeds for the cloud nodes. However, it only considers independent aperiodic real-time tasks (and not parallel applications), and it does not consider a microservice model as FTRTC does.…”
Section: Related Workmentioning
confidence: 99%
“…Some works support fault tolerance in cloud environments by scheduling backup copies of failed tasks. For example, QAFT [32] schedules primary and backup copies of tasks on different cloud nodes, considering different QoS levels for the tasks and different speeds for the cloud nodes. However, it only considers independent aperiodic real-time tasks (and not parallel applications), and it does not consider a microservice model as FTRTC does.…”
Section: Related Workmentioning
confidence: 99%
“…A dedicated VM acts as a central scheduler, responsible for scheduling the component tasks of the application jobs to the other VMs of the cloud. 28 The SaaS cloud under study is shown in Figure 1.…”
Section: System Modelmentioning
confidence: 99%
“…He et al [19] developed a rolling-horizon scheduling strategy for the energy constrained distributed real-time embedded systems. Zhu et al [62] presented a fault-tolerant scheduling algorithm called QAFT for real-time tasks with QoS needs on heterogeneous clusters. Zhu et al [63] proposed an adaptive energy-efficient scheduling, AEES, for aperiodic and independent real-time tasks on heterogeneous clusters with dynamic voltage scaling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The energy consumption by the processor of computing node can be approximated as α Δ fv t 2 [61][62][63], where f is the processor clock frequency, v is the supply voltage, Δt is the execution time, and α is a constant. The frequency is positive correlated with the voltage, and reducing voltage can lead to low frequency.…”
Section: Energy Modelmentioning
confidence: 99%